Identifikasi Komposisi Kimia Asap Cair Tandan Kosong Kelapa Sawit (TKKS) dan Kajian Literatur Potensi Insektisidanya: Identification of Chemical Composition of Liquid Smoke from Empty Fruit Bunches (EFB) and Literature Review of Its Insecticidal Potential - Sari, Yulia Padma; Santoso, Untung; Nindhiani, Faridawati Junjung; Romadhan, Panji; Tuti, Harlina Kusuma (DINAMIKA PERTANIAN, 2026)
Background: Empty oil palm bunches (EFB) are underutilized solid waste. Liquid smoke from EFB pyrolysis contains bioactive compounds as an eco-friendly natural insecticide. Objective: This study analyzes the chemical composition of EFB liquid smoke and reviews its potential as a natural insecticide against plant pests. Methods: Liquid smoke was produced by EFB pyrolysis at 150–250°C for six hours. Chemical composition was analyzed using GC-MS. A literature review (2016–2026) evaluated the insecticidal potential of identified compounds. Results: GC-MS detected 60 compounds. The 19 compounds with highest relative content belonged to phenolics, heterocyclics, organic compounds, and organic acids. Phenol was the most dominant (21.68%), followed by pyridine (5.68%), p-cresol (4.23% and 1.86%), and 2-methyl-2-cyclopenten-1-one (4.14%). Literature indicates these compounds act as natural insecticides through multiple mechanisms: direct toxicity (membrane damage, protein denaturation, enzyme inactivation), metabolic disruption (inhibition of electron transport chain and ATP production), and behavioral changes (antifeedant and attractant). Synergistic effects between phenolics and ketones or pyridine derivatives may enhance insecticidal efficacy. Conclusions: EFB liquid smoke contains 60 compounds, with 19 major compounds from phenolics, heterocyclics, organic compounds, and organic acids, showing potential as natural insecticides. However, bioassays against model pests (e.g., Spodoptera litura, Sitophilus oryzae) and phytotoxicity tests are still required